The Influence of Discovery Learning Method and Reading Interest on Explanatory Text Writing Skills - Putri Kartika Oktiana; Erizal Gani Gani (STAI Hubbulwathan Duri, 2022)
The purpose of this research is to provide a detailed account of how discovery learning affects students' capacity to write explanatory texts and how this capacity interacts with students' overall reading interests. Competence with texting and writing. Quantitative research with a quasi-experimental design is the approach of selection. The participants in this analysis were all eighth graders. Purposeful sampling was employed (Class VIII.1 as the experimental class, 30 students and class VIII.2 as the control class, 30 students). A reading interest questionnaire and an evaluation of the participant's ability to write explanatory texts served as the research instruments. Explanatory text writing ability in the experimental group was found to be greater than that of the control group (Fcount(k) = 4.91 Ft(k) = 4.20). Students in both the experimental and control groups who reported a high level of interest in reading produced better explanatory texts than those in the low-interest group (Fcount (b) = 11.47 Ftable = 4.20). Writing explanatory texts is not moderated by a combination of discovery learning and reading interest (Fcount = 0.33 Ftable 4.20).